FACTORS INFLUENCING STUDENT’S ACHIEVEMENT IN LEARNING ENGLISH OF INDONESIAN DEPARTMENT AT STKIP YAYASAN ABDI PENDIDIKAN PAYAKUMBUH - Indah Rahmalia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The purpose of this study was to find out the factors influencing student’s achievement in learning English of indonesian department at STKIP Yayasan Abdi Pendidikan Payakumbuh. This study was carried out of descriptive qualitative research by employing questionnaire and peer debriefs to check the trustworthiness of the data. It was given to 25 students from indonesian department selected by using purposive sampling technique. The findings of this study show that the highest score of the factors that influence the learning achievement of the students is the Internal factor that is Psychology factors with the score 815. It can be concluded that the psychology factors as positively atmosphere which extrinsically motivated them in learning especially in English. Keywords